Analisis Kesesuaian Visi, Misi, Tujuan dan Kurikulum Prodi Pendidikan Agama Islam Pascasarjana IAIN Lhokseumawe dan IAIN Curup - Ayu Fitria Nur Utami (Al-Mudarris, 2020)
This study aims to review the vision, mission, goals and curriculum of the Islamic Religious Education Study Program at the IAIN Lhokseumawe and IAIN Curup Postgraduate Programs. The research method used in this research is the document study method, in which the documents used as research material come from the web http://pasca.iainlhokseumawe.ac.id and http://pascgraduate.iaincurup.ac.id/. The data analysis used is descriptive qualitative analysis. The research findings show that in the management and development of higher education institutions, the Postgraduate Study Program of Islamic Religious Education in Lhokseumawe and IAIN Curup has formulated a vision, mission, objectives, and curriculum in order to improve the educational quality of these institutions. In addition, the formulation of the vision, mission, goals, and curriculum at IAIN Curup has a different formulation with IAIN Lhokseumawe. IAIN Curup wants national research-based PAI learning, while IAIN Lhokseumawe wants individuals to excel in education and be able to improve PAI services based on local wisdom. However, in this difference, the formulation of the vision, mission and goals are interconnected or continuous with each other.